2013
DOI: 10.4103/1119-3077.110145
|View full text |Cite
|
Sign up to set email alerts
|

Low birthweight delivery: Prevalence and associated factors as seen at a tertiary health facility

Abstract: Most LBW babies were preterm delivered by low parity parturient aged 25-35 years with short inter-pregnancy intervals. Effective family planning and antenatal services provided particularly for these categories of potential parturient could help to curb the incidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
10
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 11 publications
6
10
5
Order By: Relevance
“…This finding agreed with previous reports, in which most of the indicators were associated with mother’s age and inter-pregnancy intervals [23,24]. The mother’s economic situation has not been reported as an associated factor.…”
Section: Discussionsupporting
confidence: 92%
“…This finding agreed with previous reports, in which most of the indicators were associated with mother’s age and inter-pregnancy intervals [23,24]. The mother’s economic situation has not been reported as an associated factor.…”
Section: Discussionsupporting
confidence: 92%
“…The difference was not significant. This is same with the findings observed by Ugboma and Onyearugha [19] and Ezugwu et al [21]. In the low birth weight category, males and females did not have a significant difference in their mean weight.…”
Section: Low Birth Weight Babiessupporting
confidence: 92%
“…Swende found the mean birth weight to be 3.08 kg in Makurdi [23] while Adimorah et al found it to be 3.17 kg among Igbos in Nigeria [24]. All these values are lower than the one in the present study probably because preterm deliveries were excluded since preterm delivery as noted by Ugboma and Onyearugha, is a significant factor in low birth weight [19].…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…In this study, there was a significant, strong, positive correlation between birth weight and maternal and cord zinc concentrations, as found in a previous study [40]. A short inter-pregnancy interval is a risk factor for developing LBW [41-43]. Nevertheless, this factor was not significant in our study.…”
Section: Discussionsupporting
confidence: 77%